1992
DOI: 10.1001/archinte.1992.00400210018004
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Distal Polyps Detected With Flexible Sigmoidoscopy in Asymptomatic Patients

Abstract: Colorectal cancer screening should be performed with a 60-cm flexible sigmoidoscope, and distal colonic polyps or neoplasms will be detected in 25% of asymptomatic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…All patients with polyps were offered colonoscopy if there were no contraindications. We were not in a position to limit access to further investigation to individuals with adenomas or those with adenomas at greater risk of malignant transformation, such as those with larger polyps 3–5 . However, this would clearly be an issue requiring careful cost‐benefit analysis if a national programme was introduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients with polyps were offered colonoscopy if there were no contraindications. We were not in a position to limit access to further investigation to individuals with adenomas or those with adenomas at greater risk of malignant transformation, such as those with larger polyps 3–5 . However, this would clearly be an issue requiring careful cost‐benefit analysis if a national programme was introduced.…”
Section: Discussionmentioning
confidence: 99%
“…The expected prevalence of CRC or adenomas in asymptomatic subjects over the age of 50 undergoing flexible sigmoidoscopy (FS) is approximately 15% 4 . Approximately 20% of these patients also have a more proximal adenoma 5 . Case control studies have suggested a reduced mortality from CRC after flexible sigmoidsocopy 6 .…”
Section: Introductionmentioning
confidence: 99%